The Strategy of the Islamic Welfare Organization Malaysia (PERKIM) in Managing Mualaf Family Conflicts in Malaysia - Jamilah, Jamilah; Mohd Yusof, Sellyianasari Binti; Rahmawati, Erik Sabti; Aprilyanti, Melinda (De Jure: Jurnal Hukum dan Syari'ah, 2023)
The problems faced by the families of mualaf in Malaysia require serious handling and management by looking at the increasing number of mualaf every year. The National Board that has the responsibility to deal with this problem is the Council or State Department of Islamic Religion. Other non-governmental institutions are also involved in handling the problems of mualaf families such as The Islamic Welfare Organization Malaysia/ Pertubuhan Kebajikan Islam Malaysia (PERKIM) and Urusetia Saudara Kita (USK). This research will analyze the strategy of a governmental or non-governmental organization—the Islamic Welfare Organization Malaysia (PERKIM) in dealing with and managing the problems of converted families. This research is qualitative–empirical with a juridical-sociological approach. Primary data were collected from interviews with respondents located in Selampit Village, Malaysia. The results show that the PERKIM organization helps mualaf families in managing the conflicts they experience through cognitive empowerment strategies in handling and managing problems. Islamic preachers from PERKIM changed the speculations of mualaf parents who considered Islam immoral and troublesome religion by conveying da'wah bil-hikmah and da'wah fardiah through house-to-house visits and providing food, protection, education, financial and moral support. It can be concluded that the role of PERKIM in overcoming this conflict is good but not optimal, as can be seen from the activities, programs and policies in resolving the conflict.